Consumer Preferences for The Design of Smoked Fish Packaging Using Conjoint Analysis - Dwi Nurul Izzhati; Hasan Mastrisiswadi; J. Jazuli; Tita Talitha (Jurnal Ilmiah Teknik Industri, 2018)
Research on smoked fish packaging has only focused on its functional side to increase product life. Meanwhile, research on smoked fish packaging design that focuses on improving and expanding markets has never existed. Until now, smoked fish was sold without packaging even though the amount of production continued to increase. The purpose of this study was to determine consumer preferences for the design of smoked fish packaging. With the recognition of these preferences, it is expected that the smoked fish industry players can apply it so that it can increase the sale value and the number of sales. This study uses focus group discussion as a qualitative method and conjoint analysis as a quantitative method. Color, material, shape, size, brand, and additional information is the attribute chosen at the focus group discussion as a representation of smoked fish packaging to determine the level of its preference. The results of this study indicate that brands have the highest preference compared to others (importance values 30.303%).